Relevance of Representative Bureaucracy in Municipality Administration in the Republic of Lithuania - Mikalauskas, Arvydas (Socialiniai tyrimai, 2015)
The concept of representative bureaucracy is based on the significance of representativeness of bureaucracy: its sensitivity to the public interest is directly related to representativeness of public sector servants. This article clarifies the concept of representative bureaucracy as an approach that enables one to diagnose problems in the Lithuanian civil service human resources management and presents possible solutions. Primary focus is on the aspects of trust in civil servants and gender representation in the public service. Research into representative bureaucracy has highlighted the issues of human resource management that need to be addressed in municipality administration in Lithuania. The principles of representative bureaucracy are also relevant to local autonomy because of both, the possibility to involve residents into handling administrative issues (via active communication of civil servants) and efficiency of bureaucracy itself.